2010
DOI: 10.1208/s12249-010-9550-5
|View full text |Cite
|
Sign up to set email alerts
|

Porous Bioactive Glass Scaffolds for Local Drug Delivery in Osteomyelitis: Development and In Vitro Characterization

Abstract: Abstract.A new bioactive glass-based scaffold was developed for local delivery of drugs in case of osteomyelitis. Bioactive glass having a new composition was prepared and converted into porous scaffold. The bioactivity of the resulting scaffold was examined by in vitro acellular method. The scaffolds were loaded with two different drugs, an antibacterial or antifungal drug. The effects of the size of the scaffold, drug concentration, and dissolution medium on drug release were studied. The scaffolds were furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 26 publications
(36 reference statements)
3
32
0
Order By: Relevance
“…These P-O bands in the samples with 25, 50, and 75 wt.% BG due to the presence of HA, are more specific, but in the sample with 100 wt.% BG a broad band at 570-602 cm À1 was present after soaking in SBF for 28 days, implying the formation of an amorphous or thin calcium phosphate layer. Bands for the phosphate groups [39,40]. The carbonate peaks revealed that the HA contained some CO 3 2À groups in PO 4 3À sites of apatite lattice.…”
Section: Compositionmentioning
confidence: 97%
See 1 more Smart Citation
“…These P-O bands in the samples with 25, 50, and 75 wt.% BG due to the presence of HA, are more specific, but in the sample with 100 wt.% BG a broad band at 570-602 cm À1 was present after soaking in SBF for 28 days, implying the formation of an amorphous or thin calcium phosphate layer. Bands for the phosphate groups [39,40]. The carbonate peaks revealed that the HA contained some CO 3 2À groups in PO 4 3À sites of apatite lattice.…”
Section: Compositionmentioning
confidence: 97%
“…The FTIR data in Fig. 9 shows that in addition to the absorbances for bone-like apatite (bands of phosphate and carbonate groups), strong bands due to silicate groups of BG (523 cm À1 : Si-O-Si bending n 4 ; 743 and 844 cm À1 : Si-O symmetric stretching n 3 ) are present for the foams with different compositions [39,41,42]. Fig.…”
Section: Compositionmentioning
confidence: 97%
“…The spectrum was recorded at ambient temperature over a wavenumber range of 4,000-400 cm −1 at 2 cm −1 resolution 18 by averaging 64 scans.…”
Section: Physicochemical Characterization Of Vanp Crystallinity and Cmentioning
confidence: 99%
“…The peak observed in the range of 3420-3430cm -1 is associated with vibrations of absorbed water bond [7]. Results of FTIR analysis demonstrated that strong bonds of bioactive silicate glass group (795-815cm -1 : Si-O symmetric stretching v3) are observed in the foams with both composites, in addition to phosphate and carbonate groups of bone-like apatite [55][56][57][58].…”
Section: Discussionmentioning
confidence: 96%